The origins of white etching cracks and their significance to rolling bearing failures. (March 2019) - Manieri, Francesco; Stadler, Kenred; Morales-Espejel, Guillermo E.; Kadiric, Amir
Graphical abstract: Highlights: A specific stress sequence causes both WECs and 'unpredictable' failures concurrently. WECs are a symptom of this stress history and not a direct cause of failure. The relevant stress history consists of early short-lived high stress, followed by prolonged moderate stress. Damage potential of this stress history is not accounted for by Palmgren-Miner rule, hence the 'upredictable' failure lifetimes. No specific oil chemistry, SRR or frictional energy are required to form WECs. Abstract: Presence of white etching cracks has been widely associated with early failures of rolling bearings in a number of applications, with wind turbine gearbox bearings being the most frequently cited and practically significant example. Despite the recent research efforts, there is yet no universal agreement on the mechanisms of formation of these cracks and little direct evidence of their significance to bearing reliability. In an attempt to address this, this paper proposes a new theory on the origins and significance of white etching cracks. The paper provides systematic experimental evidence in support of this theory through rolling contact fatigue tests performed with AISI 52100 bearing steel specimens on a triple-disc machine over a wide range of contact conditions. The test results show that white etching cracks can be formed with base oils as well as commercially formulated transmission and engine oils. WECs were generated under slide-roll-ratios ranging from 0.05 to 0.3, under positive and negative sliding, different contact pressures and specific film thicknesses ranging from 0.1 to 0.7. No white etching areas were ever observed without the associate crack being present, and it was also shown that white etching areas themselves can be produced in a pure rubbing contact of bearing steels under both lubricated and unlubricated conditions. These results provide direct evidence that the steel transformations that exhibit themselves as white etching areas are formed through rubbing of the existing crack faces, and that the chemical composition of the lubricant and the magnitude and direction of sliding are not the primary driver of WEC formation, in contrast to literature. Instead, the results presented here show that WECs are formed through the action of a specific stress history in time via the following mechanism: (i) Short-lived high contact stresses, which can be caused by a number of factors, act in the initial stages of the component life to initiate early fatigue cracks, (ii) These high stresses cease and the contact subsequently operates under a relatively moderate nominal stress so that the early-formed cracks propagate relatively slowly and their faces rub and beat together for a prolonged period, (iii) White etching areas are formed around the existing cracks through this crack-face rubbing, (iv) Eventual contact failure occurs through pitting which can be caused by a white etching or a non-white etching crack depending on its location and propagation rate. Standard contact fatigue life models are unable to account for the adverse effects of this specific stress sequence owing to their use of linear damage accumulation rules, which leads to such failures being termed as 'premature'. The proposed theory asserts that the white etching cracks are not the cause of 'premature' bearing failures, but that both the WECs and the earlier-than-predicted bearing failures are caused simultaneously by a third factor: a specific time history of applied contact stress.